Pedagogical Principles of Foreign Language Studies - Liepa, Diāna; Špona, Ausma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Adult learners’ study process is affected by former life’s experiences: memories, various events, relations and former study habits etc. Adult learning that is based on adults‘ own initiative and responsibility have been defined in several ways: self-directed learning, self-planned studying, self-studying, independent studies, autonomous studying, autodidactics as well as open learning. Aim of the study: to propose pedagogical principles of foreign language studies. Materials and methods: analysis of scientific and methodological literature, modelling, observation, Methods of data processing and analysis: quantitative (data analysis by using the data processing software SPSS 17.0. In the Research results approve high necessity to optimise the study process taking into consideration the principles that were researched in adults’ learning and teaching.